Toxicological Impact and in Vivo Tracing of Rhodamine Functionalised ZIF-8 Nanoparticles - Goyal, Prateek; Soppina, Pushpanjali; Misra, Superb K.; Valsami-Jones, Eugenia; Soppina, Virupakshi; Chakraborty, Swaroop (Frontiers in Toxicology, 2022)
Metal Organic Frameworks (MOFs) are extensively used for a wide range of applications due to their exceptionally high surface area. MOF particles are conventionally in micron size, but the nanosized MOFs show good transportation/mobility due to their small size, and when combined with the high surface area of MOFs, it makes MOF nanoparticles an ideal candidate to study for environmental remediation. Therefore, it is important to study the ecotoxicological impact of these MOFs. In this study, we developed rhodamine labelled nanoparticles of zinc imidazolate metal organic framework as a means of in vivo tracing the MOF translocation in C. elegans. Rhodamine B isothiocyanate functionalized ZIF-8 MOFs nanoparticles (RBITC@ZIF-8 MOF nanoparticles; size 44 ± 7 nm) were fed to the worms naturally within a concentration range of 0.16-16.4 µg mg-1. Fluorescence was detected in the pharyngeal and gut lumen regions of the worms after 4 h of treatment, for exposure concentrations >0.163 µg mg -1. A higher intensity of fluorescence was observed at the end of 24 h for all exposure concentrations. Worms treated with RBITC@ZIF-8 MOF concentrations of 1.63 µg mg-1 for 24 h showed a bright stable fluorescence signal at the tail region. The uptake of RBITC@ZIF-8 MOF for an exposure concentration of 0.163 µg mg-1, 1.63 µg mg-1, and 8.2 µg mg-1 was found to be 52.1%, 11.4% and 28.6%, respectively. Through this study, we showed that RBITC@ZIF-8 MOFs can be exposed to C. elegans and imaged at low concentrations of ~0.16 µg mg-1.